(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
This article deals with methods for teaching secondary school students about the greenhouse effect. The research question is addressed in a didactic context using ICT. Our experiment used a pre-test and post-test methodology, in which we compared the learning outcomes of two groups of students: experimental group (EG) and control group (CG). Both groups followed the same teaching on the greenhouse effect during a Life and Earth Sciences (LES) class. Our study involved introduction of the following differentiation for the two groups of students: CG received explanations, accompanied by a theoretical presentation of the experiment to demonstrate the greenhouse effect. The students were then presented with the theoretical results. EG used a computer simulation of the same experiment on the greenhouse effect and interpreted the results. At post-test, the experimental group (EG) demonstrated a better understanding of the mechanisms of the greenhouse effect than the control group (CG), and scored better on questions related to infrared radiation as a result of global warming. This has been confirmed by a statistical test of homogeneity. However, on the other questions about the nature and consequences of the greenhouse effect, including on behavior advocated for the protection of the environment, we found no significant differences. Moreover, the students in both groups only proposed actions in response to the consequences of human activity and did not propose actions to respond to the consequences of natural origin. We therefore conclude that computer simulation of the greenhouse effect experiment, accompanied by further scientific interpretation, constitutes a "good didactic situation" to instill a more global understanding of the greenhouse effect.